2021
DOI: 10.23917/jiti.v20i1.12973
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Mitigation Strategy in The Halal Food Supply Chain in The Covid-19 Pandemic

Abstract: Halal is mandatory for Muslims in choosing food. During the Covid-19 pandemic, there were changes in the food supply chain system, and there was a risk of changing the status of halal to non-halal due to various sources. The research objectives are to identify halal risk activities in the supply chain, determine risk priorities and develop mitigation strategies. A case study was conducted at a fish cracker company in Sidoarjo, East Java. Data processing was performed using the FMEA method. The results showed 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
9
0
5
Order By: Relevance
“…Moreover, in halal risk assessment and mitigation approaches, some studies have been conducted to determine the potential risk activities in the supply chain. For example, Wahyuni et al (2021) conducted a study aiming to identify potential risks within the halal food supply chain. The study used failure modes and effects analysis (FMEA) and revealed nine risky activities associated with suppliers, particularly concerning labor risks due to noncompliance with halal provisions.…”
Section: Halal Meat Supply Chainmentioning
confidence: 99%
“…Moreover, in halal risk assessment and mitigation approaches, some studies have been conducted to determine the potential risk activities in the supply chain. For example, Wahyuni et al (2021) conducted a study aiming to identify potential risks within the halal food supply chain. The study used failure modes and effects analysis (FMEA) and revealed nine risky activities associated with suppliers, particularly concerning labor risks due to noncompliance with halal provisions.…”
Section: Halal Meat Supply Chainmentioning
confidence: 99%
“…By performing OEE calculations, a company will know where their position is, where the weak parts are, and how to improve [8,9]. On the other hand, FMEA is a systematic way of identifying and preventing problems in products and processes [10,11]. FMEA has been widely used, especially in the manufacturing and automotive sectors [12].…”
Section: Introductionmentioning
confidence: 99%
“…The rising trend of buying food online also affects the number of new entrepreneurs in the food sector that have sprung up in this pandemic era. Along with this, there are concerns from food buyers, especially Muslim consumers whether the products they buy are halal or haram (Wahyuni et al, 2021). Recently, halal concept is getting more interest worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The shortening of the supply chain can demonstrate the change flows due to the use of online buying and selling systems, restrictions on mass public activities, and increasing consumer demand for fast and durable food. (Wahyuni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%